Optimizing Bin Packing with Biologically Inspired Approaches: A Study on Bee Colony Optimization - Patel, Sofia; Thompson, Ethan (Journal of Computer Engineering, 2020)
—We treat the two-dimensional bin packing problem which involves packing a given set of rectangles into a minimum number of larger identical rectangles called bins. This combinatorial problem is NP-hard. We propose a pretreatment for the oriented version of the problem that allows the valorization of the lost areas in the bins and the reduction of the size problem. A heuristic method based on the strategy first-fit adapted to this problem is presented. We present an approach of resolution by bee colony optimization. Computational results express a comparison of the number of bins used with and without pretreatment